Correlation of Ramadan Fasting with HbA1C and Lipid ProfileLevel Changes in The Risk Stratification of Complications inDiabetes Mellitus Patients - Bramantya, Rinadhi Reza; Arsana, Putu Moda; Sasiarini, Laksmi (UI Scholars Hub, 2021)
Introduction. Diabetic patients will still do Ramadan fasting, which could affect the levels of HbA1C and lipid change after Ramadan. This study aimed to identify the correlation between fasting of Ramadan risk stratification with HbA1C and lipid levels diabetic patients who run the fast of Ramadan. Methods. This was a survey research using pre - post test. Study was conducted among diabetes patients who meet the criteria: carry out routine controls before and after Ramadan fasting at dr. Saiful Anwar Malang Hospital, filling in the required data, and underwent examination laboratory. Patients were grouped into moderate, high, and very high-risk stratification. Then we analyzed the HbA1C and fat levels before (pre) and after (post) Ramadan fasting in each risk group. Results. There were 25 subjects included in this study. There was a decrease in HbA1C level in all subjects from 7.93% (SD 2.3) to 7.86% (SD 1.9) after Ramadan fasting (p = 0.563), only the moderate risk group increased by 0,37% (SB 0.27). In all subjects, total cholesterol levels increased from 196.4 (SD 48.7) mg/dl to 205.0 (SB 70.8) mg/dl (p = 0.397), with the highest change found in the very high-risk group with an increase 30,7 (SD 125.0) mg/dl. There was a decrease in HDL levels from 55.6 (SD 31.3) mg/dl to 47.8 (SD 10.5) mg/dl (p = 0.782), and the highest decrease occurred in the very high - risk group (27.7 (SD 66,9) mg / dl). There was an increase in the LDL from 115.9 (SD 45.8) mg/dl to 130.4 (SD 41.9) mg/dl (p = 0.133) which the highest increase found in the very high-risk group (55.0 (SD 74.7) mg/dl). Only triglycerides showed an improvement from 190.7 (SD 105.2) mg/dl to 188.8 (SD 79.6) mg/dl (p = 0.084), increasement only occur in the high risk group (13.2 (SD 213.4) mg/dl). Conclusion. There was a decrease in HbA1C levels, but the value of the statistics was not significant. There was a negative effect of fasting Ramadan against blood-fat levels, except for improvements in the levels of triglycerides though statistically not significant